Metode Santri Putra Pondok Pesantren Menara Al-Fattah Mangusari Tulungagung dalam Menghafal Al-Qur’an - Ahmad Fahrudin; Abdul Aziz , Nashrul (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
Memorizing Al-Qur'an is a process of activity to remember and absorb verses and their meanings into the brain so that they always remember. So that in the process of memorizing the Al-Quran, a method is needed to help expedite a process of memorizing the Al-Qur'an with an appropriate memorization method that can have a good impact on students in the process of memorizing the Al-Qur'an. And the method used is a method that can be carried out repeatedly and is able to impact the completion of the target in memorizing the Qur'an in an efficient time. The purpose of this study was to determine the method of recitation, supporting and inhibiting factors, as well as efforts to overcome various difficulties faced in the Koran, and the solution. This study uses a qualitative method. Qualitative Research (Qualitative Research) is a study that aims to describe and analyze phenomena, events, social activities, attitudes, beliefs, opinions, and thoughts in individuals or groups. The results of this study were 1) When the male students of the Islamic Boarding School Putra Al-Fattah Mangunsari Tulungagung Islamic Boarding School wanted to memorize the Al-Qur'an, they did not apply a special method. 2) Difficulties encountered during the process of memorizing the Al-Qur'an can be overcome more easily with the methods used by male students.